Drivers of Customer Satisfaction Among Mountain Hikers: The Role of Product Quality, Sales Promotion, and Perceived Price - Varellino, Geraldus Edbert; Isharina, Ikhtiara Kaideni (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The objective of this research is to identify and analyze the effects of product quality, sales promotion and perceived price on the customer satisfaction of mountain hikers in Malang City. Using purposive sampling technique, 132 mountain hikers of Malang City who have made at least one purchase of Consina products were selected as the respondents. The data was harvested via Google Forms questionnaires and was analyzed through multiple linear regression in SPSS 26. This study finds that product quality, sales promotion, and perceived price partially have significant effects on the customer satisfaction. With the adjusted R-squared value of 0.601, it can be inferred that product quality, sales promotion, and perceived price influence 60.1% of the customer satisfaction, with the remaining 39.9% is the contribution of other variables not discussed in this research.